2005
DOI: 10.1071/sr04109
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of macronutrients and metals from undisturbed soils treated with metal-spiked sewage sludge. 3. Distribution of residual metals

Abstract: Sewage sludge is increasingly been applied to land in New Zealand in an attempt to recycle the valuable plant nutrients such material contains. However, there are concerns regarding the environmental fate of heavy metals contained in the sludge. This study examines the soil profile distributions of metals (Cd, Cr, Cu, Ni, Pb, Zn) in large undisturbed soil lysimeters treated with metal-spiked sewage sludge, following 3 years of drainage leachate monitoring. For 3 forest soils that had all received surface appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 17 publications
3
22
0
2
Order By: Relevance
“…The different concentrations of the analyzed metals at 20-40 cm deep (Table 3) possibly reflect a certain mobility of these elements, which was also observed by many other authors (Tiller 1989;Giusquiani et al 1992;Mbila et al 2001;McLaren et al 2005;Toribio & Romanya 2006;Antoniadis 2008). In support of this hypothesis, the organic carbon content is influenced by the doses of sewage sludge at depth (Table 2), indicating a possible mobility of organic complexes accountable for the mobilization of metals at depth (Strobel 2001;Tipping 2002;Tan 2003).…”
Section: Mehlich 1 and Dtpa Extractionssupporting
confidence: 73%
“…The different concentrations of the analyzed metals at 20-40 cm deep (Table 3) possibly reflect a certain mobility of these elements, which was also observed by many other authors (Tiller 1989;Giusquiani et al 1992;Mbila et al 2001;McLaren et al 2005;Toribio & Romanya 2006;Antoniadis 2008). In support of this hypothesis, the organic carbon content is influenced by the doses of sewage sludge at depth (Table 2), indicating a possible mobility of organic complexes accountable for the mobilization of metals at depth (Strobel 2001;Tipping 2002;Tan 2003).…”
Section: Mehlich 1 and Dtpa Extractionssupporting
confidence: 73%
“…More Cd leached out of the forest soils than the pasture soils, and this was expected from the acidic forest soils. Sludge was surface applied to the forest soils and incorporated in the top 10 cm in the pasture soils (McLaren et al, 2005). After three years, there was little movement of Cd below the level of incorporation in the pasture soils, while in the three forest soils the metal penetrated to 0.25 m from the top.…”
Section: Soil Factors That Control CD Bioavailabilitymentioning
confidence: 99%
“…Heavy metals most commonly found in biosolids are Pb, Ni, Cd, Cr, Cu, and Zn, and the metal concentrations are governed by the nature and the intensity of the industrial activity, as well as the type of process employed during the biosolids treatment [31]. Under certain conditions, metals added to soils in applications of biosolids can be leached downwards through the soil profile and can have the potential to contaminate groundwater [32]. Recent studies on some New Zealand soils treated with biosolids have shown increased concentrations of Cd, Ni, and Zn in drainage leachates [33,34].…”
Section: Biosolids and Manuresmentioning
confidence: 99%